2017
DOI: 10.1038/s41598-017-15252-5
|View full text |Cite
|
Sign up to set email alerts
|

Martensite phase stress and the strengthening mechanism in TRIP steel by neutron diffraction

Abstract: Two TRIP-aided multiphase steels with different carbon contents (0.2 and 0.4 mass%) were analyzed in situ during tensile deformation by time-of-flight neutron diffraction to clarify the deformation induced martensitic transformation behavior and its role on the strengthening mechanism. The difference in the carbon content affected mainly the difference in the phase fractions before deformation, where the higher carbon content increased the phase fraction of retained austenite (γ). However, the changes in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 45 publications
4
107
1
Order By: Relevance
“…Harjo et al 45 and Moat et al 4 , is deemed not appropriate in this case. This is because the sample and instrument design render the gauge volume of the instrument not fully filled.…”
Section: Neutron Data Treatmentmentioning
confidence: 93%
“…Harjo et al 45 and Moat et al 4 , is deemed not appropriate in this case. This is because the sample and instrument design render the gauge volume of the instrument not fully filled.…”
Section: Neutron Data Treatmentmentioning
confidence: 93%
“…The transformation involves interesting mechanical properties, from strengthening to superelasticity, and shape memory effects. [1][2][3][4] Therefore, understanding the atomistic mechanisms underlying the MT plays an important role in achieving the desired material properties. The development of the microstructure arising from these transformations is strongly governed by the crystallographic symmetry or geometry of the phases; 5,6 hence, atomistic computer simulations can be especially valuable to gain insight into the details of the phase transformation kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…These results, along with the observations on the deformed microstructures of B2 phase in similar alloys [22,23], suggested that the B2 phase in the present alloy was essentially not brittle and was capable for plastic deformation. The elastic stress in each constituent phase, i.e., the so-called phase stress [37,40,41], can be evaluated from the phase strains using Hook's law and Poisson's ratios. A simplified estimation is often used, under the assumption that the phase strain can be represented by the lattice strain of certain (hkl) planes, for evaluating the phase stress when the strain in the transverse direction is not available [41]:…”
Section: Resultsmentioning
confidence: 99%
“…The elastic stress in each constituent phase, i.e., the so-called phase stress [37,40,41], can be evaluated from the phase strains using Hook's law and Poisson's ratios. A simplified estimation is often used, under the assumption that the phase strain can be represented by the lattice strain of certain (hkl) planes, for evaluating the phase stress when the strain in the transverse direction is not available [41]:…”
Section: Resultsmentioning
confidence: 99%